2022
DOI: 10.1038/s41598-022-07743-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lemna minor supplemented diets on growth, digestive physiology and expression of fatty acids biosynthesis genes of Cyprinus carpio

Abstract: The potential nutritional value of duckweed Lemna minor (Lemnaceae) was evaluated for common carp Cyprinus carpio fry. Fish were fed diets containing five graded levels of duckweed: 0% (LM0, control), 5% (LM5), 10% (LM10), 15% (LM15) and 20% (LM20). The final weight and specific growth rate were significantly higher in LM15 and LM20 diets fed fish compared to others. Feed conversion ratio was minimum in fish fed diet LM20. Amylase activity was significantly higher in LM0 treatment. Total protease, trypsin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In this study, the higher protein level results in increased body composition of fish due to the increase of aquatic macrophyte in the diets, whereas the rise in the C. demersum level reduced the lipid. In contrast, there was not only an increase in protein in common carp, but lipid contents also showed linear relationships (p < 0.05) with increasing the amount of duckweed included in the diet (Goswami et al 2022). Similarly, Rahmah et al (2022) revealed that the body composition of Pangasius catfish protein and lipid levels increased when using 10% Azolla cristata level in catfish diets.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In this study, the higher protein level results in increased body composition of fish due to the increase of aquatic macrophyte in the diets, whereas the rise in the C. demersum level reduced the lipid. In contrast, there was not only an increase in protein in common carp, but lipid contents also showed linear relationships (p < 0.05) with increasing the amount of duckweed included in the diet (Goswami et al 2022). Similarly, Rahmah et al (2022) revealed that the body composition of Pangasius catfish protein and lipid levels increased when using 10% Azolla cristata level in catfish diets.…”
Section: Discussionmentioning
confidence: 92%
“…However, the substitution of 33% C. demersum instead of wheat bran meal reduced the final weight by 10.6% and PER by 42.3% compared to the control group. Goswami et al (2022) aimed to determine the optimum dietary Lemna minor meal inclusion level in C. carpio diets. They reported that diets supplemented with duckweed had a positive effect on growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aquaculture industry is considered as the rapidly growing food‐producing sector in the world and has raised expectations of bridging the gap between fish demand and supply 4 . The development of aquaculture industry mainly depends on the supply of high‐quality feed for farmed fish 5 . Fishmeal is a commonly used protein source in aquafeeds because of its high protein content, excellent amino acid and fatty acids profile, vitamins, minerals, digestibility, palatability and low carbohydrate content 6 .…”
Section: Introductionmentioning
confidence: 99%
“…4 The development of aquaculture industry mainly depends on the supply of high-quality feed for farmed fish. 5 Fishmeal is a commonly used protein source in aquafeeds because of its high protein content, excellent amino acid and fatty acids profile, vitamins, minerals, digestibility, palatability and low carbohydrate content. 6 However, due to excessive use, rising fish production costs (40%-60%) and limited global supply of fishmeal, it must be replaced with a sustainable alternative source of protein such as the protein-rich plants.…”
Section: Introductionmentioning
confidence: 99%